Extremes in Benthic Ecosystem Services; Blue Carbon Natural Capital Shallower Than 1000 m in Isolated, Small, and Young Ascension Island’s EEZ - Barnes, David K. A.; Sands, Chester J.; Richardson, Andrew; Smith, Ness (Frontiers in Marine Science, 2019)
Biodiversity tends to decrease with increasing isolation and reduced habitat size, and increase with habitat age. Ascension Island and its seamounts are small, isolated and relatively young, yet, within its soon-to-be designated major Marine Protected Area, harbour patchily dense life in the shallows and cold water corals in deeper waters. With few local threats, global climate related stressors (e.g. temperature and acidification) and arguably plastic pollution are key issues for its survival and continued provision of ecosystem services. We evaluate the accumulated carbon in benthos around Ascension Island’s EEZ shallower than 1000 m using data from two research cruises in 2015 and 2017 through seabed mapping, seabed camera imagery and collections of benthos using a mini-Agassiz trawl. Benthos shallower than 1000 m essentially comprises the coastal waters around Ascension Island and three seamounts (Harris-Stewart, Grattan and Un-named). There is considerable societal benefit from benthic carbon storage and sequestration through its mitigation value buffering climate change. This service is often termed ‘blue carbon’. Overall we estimate that there is at least 43,000 tonnes of blue carbon, on the 3% of Ascension Island EEZ’s seabed which is <1000 m, mainly in the form of cold coral reefs. Two thirds of that occurs around the main island of Ascension, but it is very unevenly distributed on the seabed. Seabed roughness (e.g. rocky outcrops) seems most important for the development of blue carbon hotspots. About 21% of the total blue carbon is considered to be sequestered (removed from the carbon cycle for 100+ years) = 9060 tonnes Carbon. At the 2019 Shadow Price of Carbon the proportion of CO2 considered sequestered is £29-59. As 9060 t C this is equivalent to 33,250 t CO2, which in 2019 is valued at approximately £1-2 million. With time, this increases with rising value of carbon, but also annual increment of carbon deposition, to £2-4 million by 2030. Thus even when biogeographic values of isolation, size and age are least favourable to biodiversity, the natural capital stock and future services of benthic ecosystems can be considerable and generate a quantifiable economic return on their conservation.